Design and Construction of an Accounting Information System at the Nutrition Care Center of Jember State Polytechnic - Fitriya Andriyani; Lintang Anis Bena Kinanti; Eka Yuniar; Berlina Yudha Pratiwi; Dinu Saadilah (P3M Politeknik Negeri Jember, 2026)
This research urgency of effective, efficient, and accountable financial management in the institution’s nutrition service unit. Currently, financial records are still managed manually and lack proper structure, leading to potential risks such as recording errors, difficulties in transaction tracking, and delays in financial report preparation. The main objective of this study is to design and develop an accounting information system using Microsoft Excel to facilitate transaction recording, account classification, and the automatic preparation of financial reports in an integrated manner. The system is expected to improve data accuracy, accelerate the reporting process, and enhance transparency and accountability in financial management at the Nutrition Care Center (NCC). The research applies the Research and Development (R&D) method with a system development model encompassing needs analysis, system design, implementation, verification, and maintenance. Data collection was conducted through observation, interviews with NCC managers, and documentation. The information system developed is easy to access, familiar to users, and has adequate features for building small to medium scale accounting systems. The output of this research is a prototype accounting information system ready for use by NCC, as well as a research report that can serve as the basis for developing advanced application-based systems. Furthermore, the results of this research are also expected to contribute to improving the financial governance of academic-based business units at vocational colleges.